Taxonomia das espécies de vespas parasitoides (Hymenoptera) do bicudo-do-algodoeiro, Anthonomus grandis Boheman (Coleoptera: Curculionidae) do Brasil - Corralero, Priscila Kunzendorff (2021)
A taxonomic study and a synopsis of a hymenopteran parasitoids guild of parasitoids of cotton boll weevil, Antonomus grandis Boheman (Coleoptera, Curculionidae) from Brazil are presented. A checklist of these parasitoid species was compiled from literature and databases. In addition, samples of parasitoids reared from larvae and pupae of boll weevil were studied. Eighteen hymenopterous parasitoids of egg, larvae and pupae were recorded to the guild of parasitoids of boll weevil previously to this study (Chalcidoidea: Eupelmus cyaniceps Ashmead, Eupelmus pulchriceps (Cameron), Eupelmus sp, Eurytoma sp, Eurydinoteloides incerta (Ashmead), Jaliscoa grandis (Burks), Jaliscoa hunteri (Crawford), Lymaenon litoralis (Haliday); and Ichneumonoidea: Bracon mellitor Say, Bracon vulgaris Ashmead, Bracon sp, Habrobracon hebetor (Say), Chelonus sp, Triaspis kurtogaster Martin, Urosigalphus chalcodermi Wilkinson, Urosigalphus rubicorpus (Gibson), Ichneumonidae sp, Pimpla sp). Conura fusiformis (Ashmead) (Chalcididae), Eurytoma sp (Eurytomidae) and Urosigalphus sp (Braconidae) are newly to the guild and the last two are new species to science. Here it is presented a checklist of the 21 species followed by a synopsis of related data (host, geographic distribution, previous records, diagnostic features and taxonomic comments), and an identification key.